Perbandingan Konsep Adab Menurut Ibn Hajar Al-'Asqalany dengan Konsep Pendidikan Karakter di Indonesia - Indra Fajar Nurdin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Many crises that rise in our society recently, from educationalperspective, showed that the national education system has not perform optimally yet in forming society that has both skill-intellectuality and also spirituality, self-control, personality, and good moral. That multi-dimension crises basically rooted from the decrease of nation moral quality e.g. the increase of corruption culture and conflict, the raise of criminality, and the decrease of work-ethos. A solution applied by Indonesian government is by implementing character education, that has similar term in Islamic education's the concept of Adab. The purpose of this research is to find out the concept about Adab by Ibn Hajar al-Asqalany, and to find out the comparison and relevance between Ibn Hajar al-'Asqalany's concept of Adab with the concept of character education in Indonesia. This research concludes that the concept of Adab based on Ibn Hajar al-'Asqalany's thought includes the fulfillment and development of adab to Allah Swt, adab to his/her self, and adab to another person. That concept of adab can be a basic step to determine the nine cores of character education that implemented in Indonesia.